Financial Sustainability Dipengaruhi Oleh Pengeluaran R&D Dengan Gross Margin Sebagai Variabel Intervening - Ardhi Islamudin; Riyadi, Slamet; Fadlia, Irma Nur; Setiawati, Ririt Iriani Sri (LPPM POLITEKNIK LP3I BANDUNG, 2024)
This study aims to determine the effect of Research and Development (R&D) spending on financial sustainability with marketing performance, gross margin and technological performance as moderation. The research analysis technique uses SmartPLS 4, with a population of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2022 period with a total sample of 135 from 27 companies for 5 years of observation. The sample was selected using purposive sampling method. The results of hypothesis testing show that Research and Development (R&D) spending has no significant effect on financial sustainaianability, Marketing performance cannot mediate Research and Development (R&D) spending on financial sustainability, Gross margin can mediate Research and Development (R&D) spending on financial sustainaianability, technological performance cannot mediate Research and Development (R&D) spending on financial sustainability. This study found that Research and Development (R&D) activities have been able to increase the company's effectiveness in generating revenue from products and services, so as to increase demand for goods which has an impact on company performance so that financial sustainability can be achieved.